Notes on the birds of the tidal lowlands and floodplains of South Sumatra province, Indonesia - Verheugt, W J. M; Skov, H; Danielsen, F (KUKILA, 1992)
During an environmental baseline survey of the tidal lowlands and floodplains of South Sumatra Province in 1988-89, a total of 270 bird species was recorded. This paper focuses on wetland species, including those inhabiting swamp forests. No upland forest habitats are found within the region described. The area supports a diverse avifauna, including some globally threatened species that have a core population here, notably Milky Stork Mycteria cinerea, Storm's Stork Ciconia stormi, Lesser Adjutant Leptoptilos javanicus, Black-headed Ibis Threskiomis melanocephatus and Asian Dowitcher Limnodromus semipalmatus. The coast has vital passage and wintering grounds that rank second in importance only to coastal wetlands in Bangladesh for East Palaearctic waders in terms of numbers of birds. Three species were recorded for the first time in Sumatra: Spotted Eagle Aquila clanga, Steppe/Imperial Eagle Aquila nipalensis/heliaca and Spotted Redshank Tringa erythropa, and first Sumatran breeding records were obtained for Javan Pond-heron Ardeola speciosa and White-headed Stilt Himantopus leucocephalus. A few species were observed outside their previously recorded usual habitats. The paper discusses the principal habitats of the area, and the very rapid rate of development that has occurred during the past two decades. Only one wetland area in the province has protection status, Padang-Sugihan. This Wildlife Reserve does not provide habitat for eight out of the eleven globally threatened species recorded in the study area. Consequently the establishment of two additional swamp reserves and bird sanctuary is strongly recommended.